2011
DOI: 10.3109/00048674.2010.522554
|View full text |Cite
|
Sign up to set email alerts
|

Kava: A Comprehensive Review of Efficacy, Safety, and Psychopharmacology

Abstract: While current evidence supports kava for generalized anxiety, more studies are required to assess comparative efficacy and safety (on the liver, cognition, driving, and sexual effects) versus established pharmaceutical comparators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 67 publications
1
99
0
1
Order By: Relevance
“…The pooled analysis found Kava to be effective in reducing the HAM-A total score relative to placebo (weighted mean difference = 3.9, n = 380). Another pooled analysis of six studies found an effect size of 1.1 (Cohen's d ) in favour of Kava reducing HAM-A score over placebo [64]. Those studies not included in the pooled analysis were generally congruent with this result.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The pooled analysis found Kava to be effective in reducing the HAM-A total score relative to placebo (weighted mean difference = 3.9, n = 380). Another pooled analysis of six studies found an effect size of 1.1 (Cohen's d ) in favour of Kava reducing HAM-A score over placebo [64]. Those studies not included in the pooled analysis were generally congruent with this result.…”
Section: Resultsmentioning
confidence: 75%
“…The most researched herbal medicine in the treatment of anxiety is Piper methysticum (Kava); a perennial plant native to various regions of the South Pacific [62]. The roots of the Kava plant are traditionally prepared as a water-based beverage for its medicinal properties and psychotropic effects [63].…”
Section: Resultsmentioning
confidence: 99%
“…There is no current convincing evidence for the effectiveness of homoeopathic preparations in the treatment of patients with anxiety disorders [I (M)] (Davidson et al, 2011;Pilkington et al, 2006). Kava preparations appeared to have some beneficial effects in patients with generalised anxiety disorder but have been withdrawn in many countries due to potential hepatotoxic effects [IV] (Sarris et al, 2011a (Merom et al, 2008). In panic disorder, regular exercise is marginally superior to relaxation [I (PCT)] (Wedekind et al, 2010); but less effective than either the TCA clomipramine [I (PCT)] (Broocks et al, 1998) or group CBT [II] (Hovland et al, 2012).…”
Section: Recommendations: General Aspects Of Psychological Treatmentmentioning
confidence: 99%
“…Moreover, kava has been used by Western as an alcohol replacement to reduce anxiety and give relaxation feeling and as a treatment for sleeplessness, menopausal symptoms and depression (70,73). Rhizomes and roots of kava plant were the most used parts for their psychoactive properties that include sedation, anxiolysis and relaxation (74). Accordingly, the most active constituent of kava is kavalactones or kavapyrones, which is present in high concentration in roots.…”
Section: Kava (Piper Methysticum)mentioning
confidence: 99%